Pain medications for chronic pain patients: a survey on patient satisfaction in a tertiary hospital / Nur Irnawaty Zainol - Zainol, Nur Irnawaty (2017)
Malaysia reported 7.1% local adults are suffering from chronic pain. However, published findings on patients‘ satisfaction with analgesics prescribed are lacking. The purpose of this study was to describe characteristics of chronic pain patients and pain medications, evaluate their satisfaction with the pain medications prescribed and explore the relationship between satisfaction level with patient, pain and analgesic characteristics. A cross-sectional survey was performed with the administration of a revised questionnaire consisting components of patient demography, pain medication usage, level of pain and 4 subscales within the satisfaction domain. The prescribed pain medication profile was retrieved from the institution‘s medical record. Multiple linear regression models were utilized to explore the relationship between satisfaction level and other characteristics. 107 patients with a mean age of 51.6 years participated. 34.6% reported to suffer the pain between 1 to 5 years with an average pain score of 4 within the earlier week. 55.1% prescribed with combined opioid and non-opioid pain medications. Anticonvulsants (31.8%) were mainly prescribed. More than quarter of patients (28.0%) utilizes natural products or supplements to manage their pain. The mean satisfaction score for the evaluated subscales ranged from 73.21 to 87.34 (on a scale of 0-100). The least mean scores reported were satisfaction on ‗impact of current pain medication‘ and ‗efficacy‘. Frequency of intake of analgesics and average pain score within the past one week were the significant predictors to satisfaction score. In summary, patients at the studied setting were majorly satisfied with the pain medications prescribed. Analysis of the included items provided an idea on the voids to be filled by healthcare providers to further improve the care delivered.